Sejarah Perkembangan Tarekat Qodiriyah Naqsabandiyah di Kabupaten Ogan Komering Ilir 2007-2023 - Sugiyanto Sugiyanto (Jurnal Pendidikan Educandum, 2026)
The research and writing of this article aims to reveal the History of the Development of the Qodiriyah Naqsabandiyah Order in OKI Regency 2007-2023. This is important to do because it is to reveal the history and development of the Qodiriyah Naqsabandiyah Order and its role as an Islamic organization that plays an active role in moral and religious education in society. In this research, the researcher uses qualitative research while the research approach used by the author is historical. In data collection, the researcher conducted interviews and observations. This research shows that (1) the Qadiriyah Naqsabandiyah Order is one of the orders that is still experiencing growth to date, (2) in OKI Regency, almost 95% of the Qadiriyah Naqsabandiyah Order members are men, while the remaining only 5% are women. When viewed in terms of age, 70% of the order members are over 40 years old, while the other 30% are between 18 and 39 years old.